Relationship between Physical Activity and Emotional Intelligence and Bullying Among School Children (2019)
This work aims to determine the relationship between the level of physical activity in children, emotional intelligence, and bullying. A cross-sectional cohort study was conducted on 991 children, and adolescents between ages seven and 17 years from a sample of 16 public schools in Barranquilla, Colombia. The participants completed the Physical Activity Questionnaire for children and the Physical Activity Questionnaire for adolescents, along with the My Life at School questionnaire to determine the indexes of bullying and general aggression, the risk of bullying, and positive and negative behaviors. The Trait Meta-Mood Scale-24 was used to evaluate attention, clarity, and emotional repair ability. A binary logistic regression analysis was used to determine the relationship among levels of physical activity, bullying, and emotional intelligence. A total of 65.4% of the participants had low levels of physical activity. The Bullying index was 55.6%. The students who did not regularly engage in physical activity had a higher probability of being victims of school harassment [OR 1.3 (95% CI: 1.1–1.6)] and higher levels of general aggression [OR 1.4 (95% CI: 1.1–1.8)]. Furthermore, the females who did not regularly engage in physical activity reported having less control of their feelings [OR 1.6 (95% CI: 1.1–2.5)]. The results indicate that physical activity should be encouraged in schools to prevent bullying and violence. © 2019 Sociedad Revista de Psicologia del Deporte. All rights reserved.